Papers relating to the MCC tour of Australia, 1932-1933 - Hore-Ruthven, Alexander; Marylebone Cricket Club. (Canberra : National Library of Australia, 1990)
Cables and letters concerning the MCC tour of Australia, the "body-line" controversy and the proposed tour of England by Australia, 26 Jan 1933-5 Feb 1934; plus undated notes and press cuttings. Correspondents include: Sir Walter Young (Adelaide), Lloyd Dumas (The "Advertiser", Adelaide), Sir Alexander Hore-Ruthven (London & Adel.), Sir Lesley Wilson (Brisbane), Leigh Winser (Hore-Ruthven's private secretary, Adelaide), Sir George Murray (Adelaide), P.F. Warner (London), A.W. Hodgetts (Lichfield, Kensington Park). (Sir George Murray to Hore-Ruthven, 20 March 1933 includes political news and is incomplete).
See file NLA19/1555
Positive microfilm also available.
Microfilm copy of originals held by Marylebone Cricket Club.
Keywords: Hore-Ruthven, Alexander -- Archives; Cricket -- Bowling; Cricket -- England; Cricket -- Australia; Test matches (Cricket)